Digital transformation of pawnshop business: Marketing strategy and consumer trust in facing fintech competition - Harianja, Hosianna Gracia Dei; Pardosi, Yoselin; Devitasari, Keisha Andani; Haro, Andrian (Environmental, Social, Governance and Sustainable Business, 2026)
Background: The emergence of financial technology (fintech) has fundamentally transformed Indonesia's lending landscape, creating significant challenges for traditional pawnshops. This study examines how pawnshop businesses can develop effective marketing strategies to maintain competitiveness and consumer trust amid fintech disruption. Methods: This research employs a qualitative methodology combining a systematic literature review (SLR) of 32 peer-reviewed articles (2021–2025) with a descriptive case study of PT Pegadaian. Data collection involves secondary data from Pegadaian’s annual reports (2019–2023), OJK statistics, and industry publications. Analysis utilizes explicit thematic coding through three iterative phases: open coding, thematic aggregation, and empirical triangulation to maintain interpretive reliability. Findings: The study reveals that successful pawnshop businesses integrate digital channels while maintaining their core value proposition of secure, regulated lending. Key strategies include mobile application development, simplified collateral assessments, and hybrid service models combining digital convenience with physical presence. Empirically, validated by PT Pegadaian’s annual reports and internal performance data, their strategic digital transformation successfully increased transaction volume by 43% while maintaining customer satisfaction above 80%. Results indicate that omnichannel marketing approaches yield significantly higher customer retention compared to purely digital or physical-only strategies. Conclusion: Pawnshop businesses can sustain competitive positioning through strategic digitalization that preserves fundamental trust advantages such as regulatory oversight and asset security while addressing consumer demands for speed and convenience. Novelty/Originality of this article: Unlike broader fintech studies, this research offers a unique conceptual contribution by developing a specialized omnichannel hybrid marketing matrix. It establishes a concrete strategic framework for traditional asset-backed institutions to structurally reconcile the tension between automated digital speed and physical trust mechanisms, validated by empirical data from Southeast Asia’s largest pawnshop market operator.